Abundance and distribution shifts of humpback whales (Megaptera novaeangliae) in Ísafjarðardjúp - Brown, Justin Lee, 1990- (2019)
As the planet undergoes rapid climate change, the many species that inhabit it are forced to adapt. This is seen vividly when looking at a species shifting its distribution. This process gets further complicated as one species moves into a new area. This range expansion has the potential to displace a species that has been filling a specific ecological niche in an ecosystem for a long time. These changes have been observed in both the marine and terrestrial environment. Given that these changes can affect multiple levels of an ecosystem, it was determined to be essential to begin looking into the groups of humpback whales in Ísafjarðardjúp, Iceland. These cetaceans were observed for a total of 111 hours from May to September 2018. This time was spent, primarily, onboard a whale watching vessel that operated within Ísafjarðardjúp that was equipped with a single beam echo sounder. The location of the whales was calculated by taking the ship's coordinates and heading and combine them with the observed distance of the whale from the ship and the whale’s angle to the ship about the bow of the ship. Photo-identification techniques were used to identify individual whales by creating a database of photographs in which individual whales were identified by analyzing the natural markings on their flukes. The use of a drone was intended for monitoring behavior, but no useful data was collected. As a result of these observations 34 individual humpback whales were identified, humpback whale distribution was mapped, and images of the echosounder were recorded in the presence of humpback whales. Fifteen of the observed whales were matched to other locations in Iceland or previous years in Ísafjarðardjúp. The distribution of humpback whale sightings changed month to month. Local fishermen were also consulted to gather additional data on the distribution of humpback whales and interpret the images of the echosounder. This process also confirmed the changes in humpback distribution within Ísafjarðardjúp throughout the feeding ...